2013
DOI: 10.1136/jnnp-2012-304109
|View full text |Cite
|
Sign up to set email alerts
|

Split hand syndrome in amyotrophic lateral sclerosis: different excitability changes in the thenar and hypothenar motor axons

Abstract: APB axons have physiologically higher excitability than ADM axons, and, in ALS, the hyperexcitability is more prominent in APB axons. Although cortical mechanisms would also be involved, more prominent hyperexcitability of APB axons may contribute to development of split hand, and the altered axonal properties are possibly associated with motor neuronal death in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 22 publications
4
64
1
Order By: Relevance
“…Nerve conduction velocity showed compound motor action potential recorded in APB (median nerve at wrist) to be 4.3 mV and ADM (ulnar nerve at wrist) to be 5.0 mV with ratio <1, suggestive of split hand phenomenon of ALS, normal sensory nerve action potential and normal F-wave latency in bilateral median, ulnar and femoral nerves, ruling out the possibility of multifocal motor neuropathy with conduction block. Although hyperexcitability of APB was thought to be a cause for preferential wasting, this was not observed in our patient 1. Electromyography showed evidence of active denervation with fibrillation and fasciculation potentials in bilateral APB, FDI, deltoid and quadriceps muscles.…”
Section: Descriptioncontrasting
confidence: 60%
“…Nerve conduction velocity showed compound motor action potential recorded in APB (median nerve at wrist) to be 4.3 mV and ADM (ulnar nerve at wrist) to be 5.0 mV with ratio <1, suggestive of split hand phenomenon of ALS, normal sensory nerve action potential and normal F-wave latency in bilateral median, ulnar and femoral nerves, ruling out the possibility of multifocal motor neuropathy with conduction block. Although hyperexcitability of APB was thought to be a cause for preferential wasting, this was not observed in our patient 1. Electromyography showed evidence of active denervation with fibrillation and fasciculation potentials in bilateral APB, FDI, deltoid and quadriceps muscles.…”
Section: Descriptioncontrasting
confidence: 60%
“…Also, cortical hyperexcitability, a consistent feature of ALS (Vucic et al , 2006), has been shown to be associated with the split hand in ALS (Bae et al , 2014). Peripherally, motor axons innervating abductor pollicis brevis (APB) have physiologically higher excitability than those supplying abductor digiti minimi (ADM), and peripheral hyperexcitabilty in ALS in more pronounced in APB than ADM axons (Shibuya et al , 2013).…”
Section: Als Hand Function and Mirror Neuronsmentioning
confidence: 99%
“…Studies in healthy controls have reported more prominent persistent Na + conductances and less K + currents in the APB and FDI motor axons [5], thereby suggesting that motor axons innervating the APB/FDI were hyperexcitable and prone to degeneration. Underscoring this notion were findings of more prominent hyperexcitability of APB axons in a Japanese ALS cohort [17]. In contrast, a more recent study established that axonal dysfunction was evident across the range of intrinsic hand muscles and was not consistent with a split-hand distribution [18].…”
Section: Introductionmentioning
confidence: 99%